Differential Ion Accumulation and Ion Fluxes in the Mesophyll and Epidermis of Barley - Alison J. Karley; Leigh, Roger A.; Sanders, Dale (Plant physiology (Bethesda), 2000)
In barley (Hordeum vulgare L.) leaves, differential ion accumulation commonly results in inorganic phosphate (Pi) being confined to the mesophyll and Ca2+ to the epidermis, with preferential epidermal accumulation of Cl-, Na+, and some other ions. The pattern was confirmed in this study for major inorganic anions and cations by analysis of barley leaf protoplasts. The work focused on the extent to which differences in plasma membrane ion transport processes underlie these observations. Ion transport across the plasma membrane of barley epidermal and mesophyll protoplasts was investigated electrophysiologically (by microelectrode impalement and patch clamping) and radiometrically. Data from both approaches suggested that similar types of ion-selective channels and membrane transporters, which catalyze the transport of Ca2+, K+, Na+, and Pi, exist in the plasma membrane of the two cell types. In general, the simple presence or absence of ion transporters could not explain cell-type-specific differences in ion accumulation. However, patch-clamp data suggested that differential regulation of instantaneously activating ion channels in the plasma membrane could explain the preferential accumulation of Na+ in the epidermis.